Influence of gestational age on dead space and alveolar ventilation in preterm infants ventilated with volume guarantee - Neumann, R.; Pillow, J.; Thamrin, C.; Larcombe, A.; Hall, Graham; Schulzke, S. (2015)
Background: Ventilated preterm infant lungs are vulnerable to overdistension and underinflation. The optimal ventilator-delivered tidal volume (VT) in these infants is unknown and may depend on the extent of alveolarisation at birth. Objectives: We aimed to calculate respiratory dead space (VD) from the molar mass (MM) signal of an ultrasonic flowmeter (VD,MM) in very preterm infants on volume-targeted ventilation (VT target, 4-5 ml/kg) and to study the association between gestational age (GA) and VD,MM-to-VT ratio (VD,MM/VT), alveolar tidal volume (VA) and alveolar minute volume (AMV). Methods: This was a single-centre, prospective, observational, cohort study in a neonatal intensive care unit. Tidal breathing analysis was performed in ventilated very preterm infants (GA range 23-32 weeks) on day 1 of life. Results: Valid measurements were obtained in 43/51 (87%) infants. Tidal breathing variables were analysed using multivariable linear regression. VD,MM/VT was negatively associated with GA after adjusting for birth weight Z score (p < 0.001, R2 = 0.26). This association was primarily influenced by the appliance dead space. Despite similar VT/kg and VA/kg across all studied infants, respiratory rate and AMV/kg increased with GA. Conclusions:VD,app rather than anatomical VD is the major factor influencing increased VD,MM/VT at a younger GA. A volume guarantee setting of 4-5 ml/kg in the Dräger Babylog® 8000 plus ventilator may be inappropriate as a universal target across the GA range of 23-32 weeks. Differences between measured and set VT and the dependence of this difference on GA require further investigation.